Pengaruh Harga Dan Ketersediaan Produk Terhadap Keputusan Pembelian Pada Toko Sembako Sheza Palembang - Indah Mawarni; Marita Pratisila; Nanda Revita (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
Product availability and price are one of the things that consumers consider when purchasing. Often the higher the price of a product, the more available the product is. Consumers are willing to spend more if the quality, consumer sacrifice and availability of a product are commensurate with the costs incurred. The questionnaire in this research was given to 100 consumers of the Sheza Jaya Sentosa Palembang grocery store. The analytical method used in this research is quantitative. The research results show a positive and significant influence on price and product availability on purchasing decisions at the Sheza Jaya Sentosa Palembanggrocery store.